APLIKASI THEORY OF PLANNED BEHAVIOR DALAM MENJELASKAN PERILAKU EKOLOGIS GENERASI Y DI KOTA DENPASAR - Ni Ketut Dian Suryandari; Ni Wayan Sri Suprapti; I Putu Gde Sukaatmadja (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2016)
This research aimed to examine the effect of environmental knowledge on environmental attitude;the effect ofenvironmental attitudes, subjective norms, and perceived behavioral control on ecological behavior; and thediference of environmental knowledge, environmental attitudes, and ecological behavior between male andfemale. Data collected through questionnaires distributed to 120 respondents in some nutrients club in DenpasarCity determined by purposive sampling. Hypothesis tested by using Partial Least Square and t-test. Theresults indicate that the environmental knowledge has positive and significant effect on environmentalattitude; environmental attitudes, subjective norms, and perceived behavioral control have positive andsignificant effect on ecological behavior; and there is no significant difference in environmental knowledge,environmental attitude and ecological behavior between Generation Y male and female in Denpasar City.